Pro4 prolyl peptide bond isomerization in human galectin-7 modulates the monomer-dimer equilibrum to affect function - Miller, Michelle C.; Nesmelova, Irina V.; Daragan, Vladimir A.; Ippel, Hans; Michalak, Malwina; Dregni, Aurelio; Kaltner, Herbert; Kopitz, Jürgen; Gabius, Hans-Joachim; Mayo, Kevin H. (Biochemical journal, 2020)
Human galectin-7 (Gal-7; also termed p53-induced gene 1 product) is a multifunctional effector by productive pairing with distinct glycoconjugates and protein counter-receptors in the cytoplasm and nucleus, as well as on the cell surface. Its structural analysis by NMR spectroscopy detected doubling of a set of particular resonances, an indicator of Gal-7 existing in two conformational states in slow exchange on the chemical shift time scale. Structural positioning of this set of amino acids around the P4 residue and loss of this phenomenon in the bioactive P4L mutant indicated cis-trans isomerization at this site. Respective resonance assignments confirmed our proposal of two Gal-7 conformers. Mapping hydrogen bonds and considering van der Waals interactions in molecular dynamics simulations revealed a structural difference for the N-terminal peptide, with the trans-state being more exposed to solvent and more mobile than the cis-state. Affinity for lactose or glycan-inhibitable neuroblastoma cell surface contact formation was not affected, because both conformers associated with an overall increase in order parameters (S2). At low µM concentrations, homodimer dissociation is more favored for the cis-state of the protein than its trans-state. These findings give direction to mapping binding sites for protein counter-receptors of Gal-7, such as Bcl-2, JNK1, p53 or Smad3, and to run functional assays at low concentration to test the hypothesis that this isomerization process provides a (patho)physiologically important molecular switch for Gal-7.